Porous structure insulation paper with low dielectric constant and high thermal conductivity as well as preparation method and application of porous structure insulation paper

By using silane coupling agent to treat boron nitride nanosheets and aramid nanofibers in insulating paper, and combined with the construction of metal organic frames, the problems of high dielectric constant and poor thermal conductivity of insulating paper are solved, and the problem of insulating paper is achieved. The porous structural insulating paper with low dielectric constant, high thermal conductivity and high mechanical strength is improved, and the comprehensive performance of insulating paper is improved.

CN119243519AActive Publication Date: 2025-01-03SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411606688.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-03
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The high dielectric constant of existing insulating papers leads to uneven electric field distribution, which easily leads to breakdown of insulation oil, and it is difficult to improve thermal conductivity and mechanical properties at the same time.

Method used

Boron nitride nanosheets and aramid nanofibers were treated with silane coupling agent, and the boron nitride nanosheets were electrostatically self-assembled to form a boron nitride nanosheets @ aramid nanofiber composite, and a metal organic frame was constructed on the surface of the nanocellulose, and the vacuum heat drying and Hot pressing to prepare porous structural insulating paper with low dielectric constant and high thermal conductivity.

Benefits of technology

It significantly reduces the dielectric constant of insulating paper, improves thermal conductivity and mechanical strength, forms a uniform and dense mesh structure, and jointly improves the overall performance of insulating paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243519A_ABST
    Figure CN119243519A_ABST
Patent Text Reader

Abstract

The invention discloses porous structure insulation paper with low dielectric constant and high thermal conductivity, and a preparation method and application thereof, and the preparation method comprises the following steps: step 1, processing a boron nitride nanosheet BNNS by using a silane coupling agent to obtain a silane functionalized boron nitride nanosheet fBNNS dispersion liquid; step 2, adding the fBNNS dispersion liquid into the aramid nanofiber (ANF) dispersion liquid, and carrying out electrostatic self-assembly to obtain fBNNS (at) ANF; 3, constructing a metal organic framework on the surface of the nanocellulose CNF to obtain CNF loaded with the metal organic framework; and 4, mixing the fBNNS-coated ANF obtained in the step 2 and the CNF loaded with the metal organic framework obtained in the step 3, carrying out sufficient reaction under oil bath and ultrasonic conditions, and carrying out vacuum suction filtration, vacuum thermal drying and hot pressing to obtain the required porous structure insulation paper with low dielectric constant and high thermal conductivity. The insulating paper obtained by the invention can have relatively high mechanical strength while ensuring the dielectric constant and the heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating paper, and in particular to a porous insulating paper with low dielectric constant and high thermal conductivity, a preparation method and application thereof. Background Art

[0002] As a key equipment for energy transmission and conversion in the power system, the stable operation of power transformers is directly related to the safety and stability of the power grid. The continuous increase in the voltage level of the power grid has led to an increasing demand for the voltage level, capacity and reliability of power equipment, and the transformer insulation system is also facing new challenges. At present, the oil-paper insulation mainly used in transformers is the key to determining the voltage level and capacity of transformers. Since the dielectric constant of cellulose insulating paper is usually more than twice that of insulating oil, the mismatch of the dielectric constant of oil-paper leads to uneven distribution of the electric field of oil-paper, which can easily cause the insulating oil to break down due to excessive electric field strength. In actual operation, the combined effects of multiple factors such as electricity, heat, and force will also accelerate the aging of insulation.

[0003] At present, the method of reducing the dielectric constant of insulating paper focuses on finding low dielectric constant fibers in the cellulose matrix. However, this method destroys the hydrogen bond network between cellulose and the micropores, resulting in a loose structure, and the insulating paper faces the problem of significantly reduced mechanical properties. At the same time, the thermal conductivity of the insulating paper is also difficult to improve. Therefore, how to reduce the dielectric constant of the insulating paper while improving its thermal conductivity and ensuring its mechanical properties is an urgent problem to be solved. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a porous structure insulating paper with low dielectric constant and high thermal conductivity, a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is: a method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity, comprising the following steps:

[0006] Step 1: treating boron nitride nanosheets BNNS with a silane coupling agent to obtain a silane-functionalized boron nitride nanosheet fBNNS dispersion;

[0007] Step 2: Add fBNNS dispersion into aramid nanofiber ANF dispersion to obtain fBNNS@ANF by electrostatic self-assembly;

[0008] Step 3: constructing a metal organic framework on the surface of nanocellulose CNF to obtain CNF loaded with a metal organic framework;

[0009] Step 4: The fBNNS@ANF obtained in step 2 and the CNF loaded with metal organic framework obtained in step 3 are mixed, fully reacted under oil bath and ultrasonic conditions, vacuum filtered, vacuum hot dried, and hot pressed to obtain the desired porous structure insulating paper with low dielectric constant and high thermal conductivity.

[0010] Furthermore, the silane coupling agent in step 1 is selected from one of 3-aminopropyltriethoxysilane APTES and 3-aminopropyltrimethoxysilane APTMS.

[0011] Furthermore, the silane coupling agent in step 1 is firstly subjected to a hydrolysis treatment, and the process is as follows: the silane coupling agent is fully mixed with the alcohol solution, and then fully stirred at 60°C.

[0012] Furthermore, the mass ratio of fBNNS to ANF in step 2 is 1:10.

[0013] Furthermore, the metal organic framework in step 3 is a copper metal organic framework; the preparation process of CNF loaded with the metal organic framework is as follows:

[0014] Nanocellulose CNF, trimesic acid H3BTC and copper ion salt are dissolved in solvents respectively to obtain solutions of the three substances;

[0015] The H3BTC solution and the copper ion salt solution are fully mixed, and then added into the CNF solution. After ultrasonication, stirring, centrifugation, and washing, CNF loaded with metal organic framework can be obtained.

[0016] Furthermore, the copper ion salt is one or both of Cu(NO3)2 and CuSO4; the molar ratio of H3BTC and copper ions is 2:3; the ultrasonic time is 2 to 3 hours, the stirring time is 24 hours, the centrifugal speed is 16000 rpm, and the centrifugal time is 25 minutes.

[0017] Furthermore, in step 4, the mass ratio of fBNNS@ANF to CNF loaded with metal organic framework is 2:1-4.

[0018] Furthermore, in step 4, the vacuum heat drying temperature is 150° C. and the time is 12 to 36 hours; the hot pressing temperature is 160° C., the hot pressing pressure is 15 MPa, and the hot pressing time is 8 minutes.

[0019] A porous structure insulating paper with low dielectric constant and high thermal conductivity.

[0020] The invention discloses an application of porous structure insulating paper with low dielectric constant and high thermal conductivity, wherein the insulating paper is used for preparing insulating parts of power transformers.

[0021] The beneficial effects of the present invention are:

[0022] (1) The insulating paper obtained by the present invention has a metal organic framework in situ grown on the surface of nanocellulose, and the covalent bonds are cross-linked to form a metal organic framework structure, which is conducive to the transfer of charges; at the same time, the insulating paper has a porous structure, and the orientation of polar molecules under the power frequency and the relaxation polarization caused by the interface polarization are effectively reduced, which can significantly reduce the dielectric constant of the insulating paper;

[0023] (2) Highly thermally conductive Jiyuan boron nitride nanosheets are introduced into the insulating paper obtained by the present invention. The boron nitride nanosheets and nanocellulose are evenly dispersed in the nanocellulose cross-linked network through electrostatic assembly, thus constructing an effective heat conduction channel and improving the thermal conductivity of the insulating paper;

[0024] (3) In the insulating paper obtained by the present invention, a compact two-dimensional nanofiber cross-linked network with a high aspect ratio is formed through the hydrogen bonding between the high-strength aramid nanofiber and the nanocellulose, thereby overcoming the problem that the traditional modification method easily leads to the destruction of the mechanical properties of the insulating paper, so that the insulating paper can have a higher mechanical strength while ensuring the dielectric constant and thermal conductivity;

[0025] (4) The insulating paper obtained by the present invention introduces two-dimensional boron nitride nanosheets and three-dimensional metal organic frameworks into the formed fiber cross-linking network through electrostatic self-assembly and covalent bonding. The multi-dimensional system interacts with each other to form a uniform and densely connected network structure, which synergistically improves the comprehensive performance of the insulating paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a schematic diagram of the process of preparing insulating paper.

[0027] Figure 2 This is a schematic diagram of the preparation method of CNF@Cu3(BTC)2 in the present invention.

[0028] Figure 3 These are the dielectric constant test results of the insulating papers obtained in Examples 1, 2, 3, 5, 6 and Comparative Examples 1, 5, 6, 7 of the present invention at an industrial frequency of 50 Hz.

[0029] Figure 4 Schematic diagram of thermal conductivity test results of insulation paper obtained in Examples 1, 4, 7 of the present invention and Comparative Examples 2, 3, 7.

[0030] Figure 5 It is a schematic diagram of the tensile strength test results of the insulating paper obtained in Examples 1, 2, 3, 5, 6 of the present invention and Comparative Examples 1, 4, 7.

[0031] Figure 6 It is a schematic diagram of the elastic modulus test results of the insulating paper obtained in Examples 1, 2, 3, 5, 6 of the present invention and Comparative Examples 1, 4, 7. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0033] like Figure 1 As shown, a method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity comprises the following steps:

[0034] Step 1: treating boron nitride nanosheets BNNS with a silane coupling agent to obtain a silane-functionalized boron nitride nanosheet fBNNS dispersion;

[0035] First, hexagonal boron nitride needs to be exfoliated to obtain boron nitride nanosheets BNNS; ion intercalation is used to assist liquid phase exfoliation.

[0036] The boron nitride nanosheets BNNS obtained by exfoliation are functionalized with a silane coupling agent to obtain positively charged silane-functionalized boron nitride nanosheets fBNNS. The silane coupling agent is selected from one of 3-aminopropyltriethoxysilane APTES and 3-aminopropyltrimethoxysilane APTMS; the mass of the silane coupling agent is 3-5% of the mass of the fBNNS.

[0037] Before the silane coupling agent is functionalized, the silane coupling agent is first hydrolyzed, and the process is as follows: first, an alcohol solution of the silane coupling agent is prepared, wherein the mass ratio of alcohol to water in the alcohol solution is 10:1, and the alcohol solution of the silane coupling agent is prepared by stirring in an oil bath; wherein the stirring temperature is 60°C, and the stirring time is 30 to 40 minutes. The relative ratio of the silane coupling agent and the alcohol solution can be adjusted according to actual conditions.

[0038] Step 2: Add fBNNS dispersion into aramid nanofiber ANF dispersion to obtain fBNNS@ANF by electrostatic self-assembly;

[0039] Aramid nanofiber ANF is obtained by stripping Kevlar fiber, which has a negative charge and can be electrostatically self-assembled with positively charged fBNNS to obtain the desired fBNNS@ANF.

[0040] The peeling process is as follows:

[0041] The Kevlar fibers were stripped by deprotonation in a KOH / DMSO system, and the obtained aramid nanofibers were dispersed in acetone to obtain a dispersion.

[0042] The fBNNS dispersion obtained in step 1 was injected into the ANF dispersion several times, and after all of them were added, ultrasonic treatment was performed at room temperature for 1 to 2 hours, wherein the mass ratio of fBNNS to ANF was 1:10. fBNNS@ANF was dispersed in acetone to obtain a dispersion.

[0043] Step 3: constructing a metal organic framework on the surface of nanocellulose CNF to obtain CNF loaded with a metal organic framework;

[0044] The metal organic framework is Cu3(BTC)2, and the specific preparation method is as follows Figure 2 As shown:

[0045] The trimesic acid H3BTC and the copper ion salt are respectively dissolved in dimethylformamide DMF to obtain DMF solutions of three substances, wherein the copper ion salt is one or both of Cu(NO3)2 and CuSO4.

[0046] The H3BTC solution and the copper ion salt solution were mixed and stirred at room temperature for 1 to 2 hours, and the molar ratio of H3BTC to copper ions was 2:3.

[0047] The mixed solution was added to the CNF solution, ultrasonicated for 2-3 hours at room temperature, stirred for 24 hours, centrifuged at 16000 rpm for 25 minutes, and repeatedly washed with deionized water to obtain CNF@Cu3(BTC)2. The relative ratio of CNF and trimesic acid H3BTC is related to the final dielectric constant and can be adjusted as needed.

[0048] Step 4: The fBNNS@ANF obtained in step 2 and the CNF loaded with metal organic framework obtained in step 3 are mixed, fully reacted under oil bath and ultrasonic conditions, vacuum filtered, vacuum hot dried, and hot pressed to obtain the desired porous structure insulating paper with low dielectric constant and high thermal conductivity.

[0049] The mass ratio of fBNNS@ANF CNF@Cu3(BTC)2 is 2:1-4. After stirring in an oil bath at 60°C until acetone is completely volatilized and ultrasonicated until no more bubbles are generated, vacuum filtration is performed; then vacuum heat drying is performed at 150°C for 12-36 hours. After drying, hot pressing is performed at 160°C and 15Mpa for 8 minutes to obtain the desired porous structure insulating paper with low dielectric constant and high thermal conductivity.

[0050] Unless otherwise specified in the text, the dielectric constant refers to its real value.

[0051] Example 1

[0052] A method for preparing porous structure insulating paper with low dielectric constant and high thermal conductivity comprises the following steps:

[0053] Step 1: treating boron nitride nanosheets BNNS with a silane coupling agent to obtain a silane-functionalized boron nitride nanosheet fBNNS dispersion;

[0054] First, ion intercalation assisted liquid phase exfoliation was used to obtain boron nitride nanosheets BNNS: 100 mL of a mixed solution of isopropanol and deionized water with a volume ratio of 3:1 was prepared, 1 g of hBN powder and 1 g of lithium citrate were dispersed in the mixed solution, and ultrasonic exfoliation was performed at 200W in an ultrasonic cleaner for 12 hours. The exfoliated mixed solution was placed in a reactor and hydrothermally treated at 180°C for 12 hours. After the treatment, the mixture was washed four times with deionized water, and then the obtained mixed solution was centrifuged at 1600 rpm for 25 minutes, vacuum filtered, and vacuum dried at 100°C for 24 hours to obtain BNNS.

[0055] Then, BNNS was silane functionalized: 50 mL of ethanol aqueous solution with a mass ratio of ethanol to water of 10:1 was prepared, 25 mg of 3-aminopropyltriethoxysilane APTES (the weight of the silane coupling agent was 5% of the weight of BNNS) was added thereto, and then stirred in an oil bath at 60°C for 30 minutes to complete the hydrolysis of APTES. 0.5 g of BNNS was dispersed in the hydrolyzed APTES mixed solution, and stirred in an oil bath at 80°C for 6 hours to obtain silane-functionalized BNNS (fBNNS).

[0056] The obtained mixed solution was centrifuged at 1600 rpm for 25 min, vacuum filtered, and washed six times with acetone to obtain a 1 mg / mL fBNNS / acetone dispersion system. Since the surface of fBNNS was covered with amine groups after silane functionalization, the fBNNS in the dispersion system was positively charged.

[0057] Step 2: Add fBNNS dispersion into aramid nanofiber ANF dispersion to obtain fBNNS@ANF by electrostatic self-assembly;

[0058] First, Kevlar fibers were stripped to obtain aramid nanofibers ANF: Kevlar fibers were cut into small pieces of about 1 cm, placed in acetone, and ultrasonically treated for 12 h. After the ultrasonic treatment, the mixture was filtered, and the filtered Kevlar fiber blocks were dried at 65 ° C for 3 days. After drying, 1g Kevlar fiber and 1.5g KOH were dispersed in 500mL dimethyl sulfoxide (DMSO) and stirred at 800rpm at room temperature for 14d. Through deprotonation, the hydrogen bonding between nanofibers was destroyed, and 3mg / mL ANF / DMSO dispersion was obtained by stripping. Take 100mL of the dispersion, filter and disperse the ANF in acetone, wash it with acetone 6 times through a Buchner funnel, and finally dissolve the ANF in 300mL acetone and shear it with a shearing machine at 1400rpm for 15min to obtain a 1mg / mL ANF / acetone solution. The ANF in the dispersion is negatively charged.

[0059] Then, the fBNNS dispersion was mixed with the ANF dispersion for self-assembly: 60 mL of the prepared ANF / acetone solution was taken into a beaker, and 6 mL of the fBNNS / acetone solution was injected into the ANF / acetone in batches using a pipette, with 1 mL injected each time. The mixed solution was ultrasonically treated at 200 W for 2 h, and then stirred at 300 rpm for 2 h at room temperature. Through the electrostatic interaction between the negatively charged ANF and the positively charged fBNNS, and the hydrogen bonds formed by the amine groups on the surface of fBNNS and the amide groups, carboxyl groups, and amine groups on the surface of ANF, self-assembly was achieved under the action of ultrasound and stirring to obtain fBNNS@ANF.

[0060] Step 3: constructing a metal organic framework on the surface of nanocellulose CNF to obtain CNF loaded with a metal organic framework;

[0061] Weigh 37.5 mg CuSO4·5H2O, 21 mg H3BTC, and 3 g 2 wt% CNF reagent, respectively, dissolve in 10 mL DMF, and stir at 400 rpm for 2 h at room temperature. Add the CuSO4 dispersion to the stirring H3BTC solution several times, and continue stirring at room temperature for 2 h. Then add the mixed solution to the stirring CNF dispersion several times, then ultrasonically treat at 200 W for 3 h and stir at 400 rpm for 24 h. After stirring, centrifuge the mixed solution at 16000 rpm for 25 min, vacuum filter, and wash it repeatedly with deionized water six times to obtain CNF@Cu3(BTC)2. Dissolve CNF@Cu3(BTC)2 in 100 mL of deionized water.

[0062] Step 4: The fBNNS@ANF obtained in step 2 and the CNF loaded with metal organic framework obtained in step 3 are mixed, fully reacted under oil bath and ultrasonic conditions, vacuum filtered, vacuum hot dried, and hot pressed to obtain the desired porous structure insulating paper with low dielectric constant and high thermal conductivity.

[0063] The fBNNS@ANF / acetone dispersion was added to the CNF@Cu3(BTC)2 solution, and the mixture was stirred in an oil bath at 60°C to fully remove the acetone in the mixture to obtain an aqueous solution of fBNNS@ANF / CNF@Cu3(BTC)2. The mixed solution was sheared at a speed of 14000rpm for 15min, and then ultrasonically treated at 200W for 20min to fully remove the bubbles in the mixture system. The BNNS@ANF / CNF@CuBTC film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150°C for 24h. After drying, hot pressing was performed at 160°C and 15Mpa for 8min to obtain the porous structure insulating paper with low dielectric constant and high thermal conductivity.

[0064] Example 2

[0065] The other steps of this embodiment are the same as those of embodiment 1, except that in step 2, the amount of ANF / acetone solution is 80 mL; the amount of fBNNS / acetone solution is 8 mL, and in step 3, the amount of CNF reagent is 2 g.

[0066] Example 3

[0067] The other steps of this embodiment are the same as those of embodiment 1, except that in step 2, the amount of ANF / acetone solution is 40 mL; the amount of fBNNS / acetone solution is 4 mL, and in step 3, the amount of CNF reagent is 4 g.

[0068] Example 4

[0069] The other steps of this embodiment are the same as those of embodiment 1, except that the silane coupling agent used in step 1 is 3-aminopropyltrimethoxysilane APTMS.

[0070] Example 5

[0071] The other steps of this embodiment are the same as those of embodiment 1, except that the vacuum heat drying time in step 4 is 12 hours.

[0072] Example 6

[0073] The other steps of this embodiment are the same as those of embodiment 1, except that the vacuum heat drying time in step 4 is 36 hours.

[0074] Example 7

[0075] The other steps of this example are the same as those of Example 1, except that the ultrasonic treatment time of the mixed solution of fBNNS and ANF in step 2 is 1 h.

[0076] Comparative Example 1

[0077] The other steps of this embodiment are the same as those of embodiment 1, except that vacuum heat drying is not performed in step 4.

[0078] Comparative Example 2

[0079] A method for preparing insulating paper comprises the following steps:

[0080] Step 1: First, use ion intercalation assisted liquid phase exfoliation to obtain boron nitride nanosheets BNNS: prepare 100 mL of a mixed solution with a volume ratio of isopropanol and deionized water of 3:1, disperse 1 g of hBN powder and 1 g of lithium citrate in the mixed solution, and ultrasonically exfoliate at 200 W in an ultrasonic cleaner for 12 hours. Place the exfoliated mixed solution in a reactor and hydrothermally treat it at 180°C for 12 hours. After the treatment, wash the mixture six times with acetone to obtain a 1 mg / mL BNNS / acetone dispersion system.

[0081] Step 2: First, the Kevlar fiber is stripped to obtain aramid nanofiber ANF: the Kevlar fiber is cut into small pieces of about 1 cm, placed in acetone, and ultrasonically treated for 12 hours. After the ultrasonic treatment, the mixture is filtered, and the filtered Kevlar fiber blocks are dried at 65°C for 3 days. After drying, 1g of Kevlar fiber and 1.5g of KOH are dispersed in 500mL of dimethyl sulfoxide (DMSO) and stirred at 800rpm at room temperature for 14d. Through deprotonation, the hydrogen bonding between the nanofibers is destroyed, and 3mg / mL of ANF / DMSO dispersion is obtained by stripping. Take 100mL of the dispersion, filter it, disperse the ANF in acetone, wash it with acetone 6 times through a Buchner funnel, and finally dissolve the ANF in 300mL of acetone and shear it with a shearing machine at 1400rpm for 15min to obtain a 1mg / mL ANF / acetone solution. The ANF in the dispersion is negatively charged.

[0082] Step 3: constructing a metal organic framework on the surface of nanocellulose CNF to obtain CNF loaded with a metal organic framework;

[0083] Weigh 37.5 mg CuSO4·5H2O, 21 mg H3BTC, and 3 g 2 wt% CNF reagent, respectively, dissolve in 10 mL DMF, and stir at 400 rpm for 2 h at room temperature. Add the CuSO4 dispersion to the stirring H3BTC solution several times, and continue stirring at room temperature for 2 h. Then add the mixed solution to the stirring CNF dispersion several times, then ultrasonically treat at 200 W for 3 h and stir at 400 rpm for 24 h. After stirring, centrifuge the mixed solution at 16000 rpm for 25 min, vacuum filter, and wash it repeatedly with deionized water six times to obtain CNF@Cu3(BTC)2. Dissolve CNF@Cu3(BTC)2 in 100 mL of deionized water.

[0084] Step 4: Take 60mL of ANF dispersion and 6mL of BNNS dispersion, add them to the CNF@Cu3(BTC)2 solution, stir in an oil bath at 60°C, fully remove the acetone in the mixture, and obtain an aqueous solution of BNNS / ANF / CNF@Cu3(BTC)2. Shear the mixed solution at a speed of 14000rpm for 15min, and then ultrasonically treat it at 200W for 20min to fully remove the bubbles in the mixture system. The BNNS / ANF / CNF@CuBTC film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150°C for 24h. After drying, hot press at 160°C and 15Mpa for 8min to obtain the BNNS / ANF / CNF@Cu3(BTC)2 insulating paper.

[0085] Comparative Example 3

[0086] A method for preparing insulating paper comprises the following steps:

[0087] Step 1: First, the Kevlar fiber is stripped to obtain aramid nanofiber ANF: the Kevlar fiber is cut into small pieces of about 1 cm, placed in acetone, and ultrasonically treated for 12 hours. After the ultrasonic treatment, the mixture is filtered, and the filtered Kevlar fiber blocks are dried at 65°C for 3 days. After drying, 1g of Kevlar fiber and 1.5g of KOH are dispersed in 500mL of dimethyl sulfoxide (DMSO) and stirred at 800rpm at room temperature for 14d. Through deprotonation, the hydrogen bonding between the nanofibers is destroyed, and 3mg / mL of ANF / DMSO dispersion is obtained by stripping. Take 100mL of the dispersion, filter it, disperse the ANF in acetone, wash it with acetone 6 times through a Buchner funnel, and finally dissolve the ANF in 300mL of acetone, shear it with a shearing machine at 1400rpm for 15min to obtain a 1mg / mL ANF / acetone solution, and the ANF in the dispersion is negatively charged.

[0088] Step 2: constructing a metal organic framework on the surface of nanocellulose CNF to obtain CNF loaded with a metal organic framework;

[0089] Weigh 37.5 mg CuSO4·5H2O, 21 mg H3BTC, and 3 g 2 wt% CNF reagent, respectively, dissolve in 10 mL DMF, and stir at 400 rpm for 2 h at room temperature. Add the CuSO4 dispersion to the stirring H3BTC solution several times, and continue stirring at room temperature for 2 h. Then add the mixed solution to the stirring CNF dispersion several times, then ultrasonically treat at 200 W for 3 h and stir at 400 rpm for 24 h. After stirring, centrifuge the mixed solution at 16000 rpm for 25 min, vacuum filter, and wash it repeatedly with deionized water six times to obtain CNF@Cu3(BTC)2. Dissolve CNF@Cu3(BTC)2 in 100 mL of deionized water.

[0090] Step 3: Take 60mL of ANF dispersion, add it to the CNF@Cu3(BTC)2 solution, stir it in an oil bath at 60°C, fully remove the acetone in the mixture, and obtain an aqueous solution of ANF / CNF@Cu3(BTC)2. Shear the mixed solution at a speed of 14000rpm for 15min, and then ultrasonically treat it at 200W for 20min to fully remove the bubbles in the mixture system. The ANF / CNF@Cu3(BTC)2 film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150°C for 24h. After drying, hot press at 160°C and 15Mpa for 8min to obtain the ANF / CNF@Cu3(BTC)2 insulating paper.

[0091] Comparative Example 4

[0092] A method for preparing insulating paper comprises the following steps:

[0093] Step 1: First, use ion intercalation assisted liquid phase exfoliation to obtain boron nitride nanosheets BNNS: prepare 100 mL of a mixed solution with a volume ratio of isopropanol and deionized water of 3:1, disperse 1 g of hBN powder and 1 g of lithium citrate in the mixed solution, and ultrasonically exfoliate at 200 W in an ultrasonic cleaner for 12 hours. Place the exfoliated mixed solution in a reactor and hydrothermally treat it at 180°C for 12 hours. After the treatment, wash the mixture six times with acetone to obtain a 1 mg / mL BNNS / acetone dispersion system.

[0094] Step 2: Weigh 37.5 mg CuSO4·5H2O, 21 mg H3BTC, and 3 g 2 wt% CNF reagent, dissolve them in 10 mL of DMF, and stir at 400 rpm for 2 h at room temperature. Add the CuSO4 dispersion to the stirring H3BTC solution several times, and continue stirring at room temperature for 2 h. Then add the mixed solution to the stirring CNF dispersion several times, then ultrasonically treat at 200 W for 3 h and stir at 400 rpm for 24 h. After stirring, centrifuge the mixed solution at 16000 rpm for 25 min, vacuum filter, and wash it repeatedly with deionized water six times to obtain CNF@Cu3(BTC)2. Dissolve CNF@Cu3(BTC)2 in 100 mL of deionized water.

[0095] Step 3: Take 6mL of BNNS dispersion, add it to the CNF@Cu3(BTC)2 solution, stir it in an oil bath at 60°C, fully remove the acetone in the mixture, and obtain an aqueous solution of BNNS@Cu3(BTC)2. Shear the mixed solution at a speed of 14000rpm for 15min, and then ultrasonically treat it at 200W for 20min to fully remove the bubbles in the mixture system. The BNNS@Cu3(BTC)2 film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150°C for 24h. After drying, hot press at 160°C and 15Mpa for 8min to obtain the BNNS@Cu3(BTC)2 insulating paper.

[0096] Comparative Example 5

[0097] A method for preparing insulating paper comprises the following steps:

[0098] Step 1: Use ion intercalation assisted liquid phase exfoliation to obtain boron nitride nanosheets BNNS: prepare 100mL of a mixed solution with a volume ratio of isopropanol and deionized water of 3:1, disperse 1g of hBN powder and 1g of lithium citrate in the mixed solution, and ultrasonically exfoliate at 200W in an ultrasonic cleaner for 12h. The exfoliated mixed solution is placed in a reactor and hydrothermally treated at 180℃ for 12h. After the treatment, the mixture is washed four times with deionized water, and then the obtained mixed solution is centrifuged at 1600rpm for 25min, vacuum filtered, and vacuum dried at 100℃ for 24h to obtain BNNS.

[0099] Then, BNNS was silane functionalized: 50 mL of ethanol aqueous solution with a mass ratio of ethanol to water of 10:1 was prepared, 25 mg of 3-aminopropyltriethoxysilane APTES (the weight of the silane coupling agent was 5% of the weight of BNNS) was added thereto, and then stirred in an oil bath at 60°C for 30 minutes to complete the hydrolysis of APTES. 0.5 g of BNNS was dispersed in the hydrolyzed APTES mixed solution, and stirred in an oil bath at 80°C for 6 hours to obtain silane-functionalized BNNS (fBNNS).

[0100] The obtained mixed solution was centrifuged at 1600 rpm for 25 min, vacuum filtered, and washed six times with acetone to obtain a 1 mg / mL fBNNS / acetone dispersion system. Since the surface of fBNNS was covered with amine groups after silane functionalization, the fBNNS in the dispersion system was positively charged.

[0101] Step 2: Add fBNNS dispersion into aramid nanofiber ANF dispersion to obtain fBNNS@ANF by electrostatic self-assembly;

[0102] First, Kevlar fibers were stripped to obtain aramid nanofibers ANF: Kevlar fibers were cut into small pieces of about 1 cm, placed in acetone, and ultrasonically treated for 12 h. After the ultrasonic treatment, the mixture was filtered, and the filtered Kevlar fiber blocks were dried at 65 ° C for 3 days. After drying, 1g Kevlar fiber and 1.5g KOH were dispersed in 500mL dimethyl sulfoxide (DMSO) and stirred at 800rpm at room temperature for 14d. Through deprotonation, the hydrogen bonding between nanofibers was destroyed, and 3mg / mL ANF / DMSO dispersion was obtained by stripping. Take 100mL of the dispersion, filter and disperse the ANF in acetone, wash it with acetone 6 times through a Buchner funnel, and finally dissolve the ANF in 300mL acetone and shear it with a shearing machine at 1400rpm for 15min to obtain a 1mg / mL ANF / acetone solution. The ANF in the dispersion is negatively charged.

[0103] Then, the fBNNS dispersion was mixed with the ANF dispersion for self-assembly: 60 mL of the prepared ANF / acetone solution was taken into a beaker, and 6 mL of the fBNNS / acetone solution was injected into the ANF / acetone in batches using a pipette, with 1 mL injected each time. The mixed solution was ultrasonically treated at 200 W for 2 h, and then stirred at 300 rpm for 2 h at room temperature. Through the electrostatic interaction between the negatively charged ANF and the positively charged fBNNS, and the hydrogen bonds formed by the amine groups on the surface of fBNNS and the amide groups, carboxyl groups, and amine groups on the surface of ANF, self-assembly was achieved under the action of ultrasound and stirring to obtain fBNNS@ANF.

[0104] Step 3: Weigh 3g of 2wt% CNF reagent and dissolve it in 100mL of deionized water, and stir at 400rpm for 30min at room temperature. Add the fBNNS@ANF / acetone dispersion to the CNF solution, stir in an oil bath at 60°C, fully remove the acetone in the mixture, and obtain an aqueous solution of fBNNS@ANF / CNF. Shear the mixed solution at a speed of 14000rpm for 15min, and then ultrasonically treat it at 200W for 20min to fully remove the bubbles in the mixture system. The fBNNS@ANF / CNF film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150°C for 24h. After drying, hot press at 160°C and 15Mpa for 8min to obtain the fBNNS@ANF / CNF insulating paper.

[0105] Comparative Example 6

[0106] A method for preparing insulating paper comprises the following steps:

[0107] Step 1: Kevlar fiber is stripped to obtain aramid nanofiber ANF: Kevlar fiber is cut into small pieces of about 1 cm, placed in acetone, and ultrasonically treated for 12 hours. After the ultrasonic treatment, the mixture is filtered, and the filtered Kevlar fiber blocks are dried at 65°C for 3 days. After drying, 1g Kevlar fiber and 1.5g KOH are dispersed in 500mL dimethyl sulfoxide (DMSO) and stirred at 800rpm at room temperature for 14d. Through deprotonation, the hydrogen bonding between nanofibers is destroyed, and 3mg / mL ANF / DMSO dispersion is obtained by stripping. Take 100mL of the dispersion, filter and disperse the ANF in acetone, wash it with acetone 6 times through a Buchner funnel, and finally dissolve the ANF in 300mL acetone, shear it with a shearing machine at 1400rpm for 15min to obtain a 1mg / mL ANF / acetone solution, and the ANF in the dispersion is negatively charged.

[0108] Step 2: Weigh 3g of 2wt% CNF reagent, dissolve it in 50mL of deionized water, and stir at 400rpm for 2h at room temperature. Take 60mL of ANF solution, add it to the CNF solution, stir at 400rpm for 1h at room temperature, shear the mixed solution at a speed of 14000rpm for 15min, and then ultrasonically treat it at 200W for 20min to fully remove the bubbles in the mixture system. The ANF / CNF film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150°C for 24h. After drying, hot press at 160°C and 15Mpa for 8min to obtain the ANF / CNF insulating paper.

[0109] Comparative Example 7

[0110] Weigh 6g of 2wt% CNF reagent, dissolve it in 50mL of deionized water, and stir it at 400rpm for 2h at room temperature. Shear the mixed solution at a speed of 14000rpm for 15min, and then ultrasonicate it at 200W for 20min to fully remove the bubbles in the mixture system. The CNF film was prepared by vacuum-assisted filtration, and then vacuum-dried at 150℃ for 24h. After drying, hot press at 160℃ and 15Mpa for 8min to obtain the CNF insulating paper.

[0111] Figure 3 It is a schematic diagram of the statistical results of the dielectric constants of Examples 1, 2, 3, 5, 6 and Comparative Examples 1, 5, 6, 7 at an industrial frequency of 50 Hz.

[0112] As can be seen from the figure, Example 1 and Comparative Examples 5, 6, and 7 show that the introduction of the metal organic framework CNF@Cu3(BTC)2 constructed on the surface of CNF can significantly reduce the dielectric constant of the insulating paper. From the comparison of Examples 1, 2, and 3, it can be seen that as the proportion of CNF@Cu3(BTC)2 increases, the dielectric constant of the insulating paper further decreases.

[0113] from Figure 3It can be seen that by adjusting the ratio of fBNNS@ANF to CNF@Cu3(BTC)2, the dielectric constant of the insulating paper can be regulated. When the mass ratio of fBNNS@ANF to CNF@Cu3(BTC)2 in Example 1 is 1:1, the dielectric constant of the insulating paper obtained is 2.21, which is approximately equal to the dielectric constant of the insulating oil, and can effectively avoid the mismatch of the dielectric constant of the oil-paper, resulting in uneven distribution of the oil-paper electric field, and the insulation oil is subjected to excessive electric field strength and breakdown. It can be seen from the results of Examples 1, 5, 6 and Comparative Example 1 that with the extension of the vacuum heat drying time, the dielectric constant of the insulating paper decreases; vacuum heat drying can effectively remove water molecules in the metal organic framework to form a high-porosity structure. The removal of polar water molecules and the introduction of air with a low dielectric constant can effectively reduce the relaxation polarization caused by the orientation of polar water molecules and interfacial polarization at the power frequency, and reduce the dielectric constant of the insulating paper.

[0114] Figure 4 The thermal conductivity test results of the insulating paper obtained in Examples 1, 4, 7 and Comparative Examples 2, 3, and 7 of the present invention are shown in the figure. It can be seen from the figure that the thermal conductivity of the insulating paper obtained in Example 1 is 6.21 W / m·K, and the thermal conductivity of the insulating paper in Comparative Example 7 is 2.17 W / m·K; compared with the ordinary nanocellulose insulating paper in Comparative Example 7, its thermal conductivity is increased by 186%. The thermal conductivity of the insulating paper obtained in Comparative Example 3 is 1.87 W / m·K, which is 232% higher than that in Comparative Example 3. It can be seen from the results that the introduction of high thermal conductivity nanomaterial fBNNS can construct an effective thermal conductive network and significantly improve the thermal conductivity of the insulating paper.

[0115] From the results of Examples 1 and 4, it can be seen that the effect of silane functionalization of fBNNS treated with coupling agent APTES is better than that of APTMS. From the results of Examples 1 and 7, it can be seen that a longer ultrasonic treatment time can make the electrostatic self-assembly of fBNNS and ANF more complete, avoid the agglomeration of fBNNS, achieve its uniform dispersion in the network, and significantly improve the thermal conductivity of the insulating paper. However, the insulating paper in Comparative Example 2 did not undergo self-assembly of BNNS and ANF. Since BNNS is easy to agglomerate, adding it alone makes the thermal conductive network defective, and the thermal conductivity of the insulating paper is significantly lower than that of Example 1.

[0116] Figure 5 The tensile strength test results of the insulating paper were obtained for Examples 1, 2, 3, 5, 6 and Comparative Examples 1, 4, 7. Figure 6 It can be seen from the figure that the mechanical properties of each embodiment are significantly improved compared with the ordinary nanocellulose insulation paper.

[0117] from Figure 5 and Figure 6By comparing the results of Examples 1, 2, and 3 with Comparative Example 4, it can be seen that the mechanical properties of the insulating paper gradually improve with the increase of the fBNNS@ANF content. Because ANF has excellent mechanical strength and a large aspect ratio. At the same time, hydrogen bonds can be formed between ANF and CNF, and ANF forms a nano-network skeleton in the insulating paper, so it can effectively realize the load transfer and improve the mechanical properties of ordinary cellulose insulating paper. In the range of the mass ratio of fBNNS@ANF to CNF@Cu3(BTC)2 of the present invention is 2: (1 to 4), the content of ANF is positively correlated with the mechanical properties of the insulating paper.

[0118] From the results of Examples 1, 5, 6 and Comparative Example 1, it can be seen that as the vacuum heat drying time increases, the mechanical properties of the insulating paper show a downward trend. This is because the vacuum heat drying effectively removes water molecules in the porous structure of the insulating paper and introduces more cavities. The cavity structure significantly reduces the dielectric constant and also reduces its mechanical strength to a certain extent, but it is still significantly improved compared with traditional cellulose insulating paper. The insulating paper obtained by the present invention can maintain its mechanical strength at a high level while significantly reducing its dielectric constant and improving thermal conductivity.

[0119] The present invention obtains an ANF-CNF two-dimensional nanofiber cross-linked network through hydrogen bonding between aramid nanofibers and nanocellulose. The network provides sufficient active sites for the growth of Cu3(BTC)2 metal organic framework, helps to build a densely connected porous network structure, and is conducive to the transfer of charge; at the same time, the porous structure of the metal organic framework can effectively prevent the agglomeration of nanofibers, and is conducive to the uniform dispersion of self-assembled nano high thermal conductivity elementary boron nitride nanosheets in space, thereby facilitating the construction of the overall stress transfer network and the thermal conductive network, and improving the mechanical properties and thermal conductivity of the insulating paper.

[0120] The aramid nanofibers and CNF in the insulating paper obtained by the present invention interact to form a three-dimensional fiber cross-linked network; wherein the Cu3(BTC)2 metal organic framework also provides a three-dimensional multi-porous structure, and the two-dimensional high thermal conductivity boron nitride nanosheets are uniformly dispersed in the multi-dimensional system structure; multiple substances and multi-dimensional system structure are interconnected, and the dielectric properties, mechanical properties and thermal conductivity of the insulating paper are synergistically improved. Vacuum heat drying is used to remove water molecules in the framework to form a high-porous structure, reduce relaxation polarization, and significantly reduce the dielectric constant of the insulating paper; the dielectric constant is regulated by regulating the ratio of fBNNS@ANF and CNF@Cu3(BTC)2, and the insulating paper with a dielectric constant approximately equal to that of the insulating oil is prepared, which can effectively avoid the problem of uneven electric field distribution of the oil-paper due to the mismatch of the dielectric constant of the oil-paper and the breakdown of the insulating oil due to excessive electric field intensity.

Claims

1. A method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity, characterized in that: The following steps are involved: Step 1: treating boron nitride nanosheets BNNS with a silane coupling agent to obtain a silane-functionalized boron nitride nanosheet fBNNS dispersion; Step 2: Add fBNNS dispersion into aramid nanofiber ANF dispersion to obtain fBNNS@ANF by electrostatic self-assembly; Step 3: constructing a metal organic framework on the surface of nanocellulose CNF to obtain CNF loaded with a metal organic framework; Step 4: The fBNNS@ANF obtained in step 2 and the CNF loaded with metal organic framework obtained in step 3 are mixed, fully reacted under oil bath and ultrasonic conditions, vacuum filtered, vacuum hot dried, and hot pressed to obtain the desired porous structure insulating paper with low dielectric constant and high thermal conductivity.

2. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 1, characterized in that: The silane coupling agent in step 1 is selected from one of 3-aminopropyltriethoxysilane APTES and 3-aminopropyltrimethoxysilane APTMS.

3. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 1, characterized in that: The silane coupling agent in step 1 is firstly subjected to a hydrolysis treatment, and the process is as follows: the silane coupling agent is fully mixed with the alcohol solution, and the mixture is fully stirred at 60°C.

4. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 1, characterized in that: The mass ratio of fBNNS to ANF in step 2 is 1:

10.

5. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 1, characterized in that: The metal organic framework in step 3 is a copper metal organic framework; the preparation process of CNF loaded with the metal organic framework is as follows: Nanocellulose CNF, trimesic acid H3BTC and copper ion salt are dissolved in solvents respectively to obtain solutions of the three substances; The H3BTC solution and the copper ion salt solution are fully mixed, and then added into the CNF solution. After ultrasonication, stirring, centrifugation, and washing, CNF loaded with metal organic framework can be obtained.

6. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 5, characterized in that: The copper ion salt is one or two of Cu(NO3)2 and CuSO4; the molar ratio of H3BTC to copper ions is 2:3; the ultrasonic time is 2 to 3 hours, the stirring time is 24 hours, the centrifugal speed is 16000 rpm, and the centrifugal time is 25 minutes.

7. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 1, characterized in that: In step 4, the mass ratio of fBNNS@ANF to CNF loaded with metal organic framework is 2:1-4.

8. The method for preparing a porous structure insulating paper with low dielectric constant and high thermal conductivity according to claim 1, characterized in that: In step 4, the vacuum heat drying temperature is 150° C. and the time is 12 to 36 hours; the hot pressing temperature is 160° C., the hot pressing pressure is 15 MPa, and the hot pressing time is 8 minutes.

9. A porous insulating paper with low dielectric constant and high thermal conductivity obtained by the preparation method of any one of claims 1 to 8.

10. The use of a porous structure insulating paper with low dielectric constant and high thermal conductivity as claimed in claim 9, characterized in that: The insulating paper is used for preparing insulating parts of power transformers.

Citation Information

Patent Citations

  • Cellulose nanofibril / metal-organic framework composite lithium ion battery separator and preparation method

    CN108428841A

  • Nano aramid / boron nitride heat-conduction thin film with low dielectric constant and preparation method thereof

    CN109721750A

  • Nanocomposite material battery diaphragm, preparation method thereof and lithium battery

    CN115036646A

  • Preparation method and application of composite aramid paper for high-frequency working condition

    CN118273163A

  • Additives for Dehydration Reaction of 1―Alcohol and Method for Preparing 1―Olefin Using the Same

    KR1020220102021A